PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH YANG DIMEDIASI OLEH KEPERCAYAAN DAN KEPUASAN PADA BANK ACEH SYARIAH CABANG ACEH BESAR - Muzaiyanah muzaiyanah; Fakhrurrazi Fakhrurrazi (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to measure the Effect of Service Quality on Customer Loyalty mediated by Trust and Satisfaction at Bank Aceh Syariah Aceh Besar Branch. The sample used in this study was the customers of Bank Aceh Syariah Branch of Aceh Besar, amounting to 200 respondents. The data collection equipment used in this study was a questionnaire. The sampling technique used is purposive sampling. Structural Equation Modeling (SEM) is used as an analytical method to determine the effect between the variables involved. Based on the results of SEM analysis, it is identified that service quality affects customer loyalty at Bank Aceh Syariah Aceh Besar Branch, service quality affects customer satisfaction at Bank Aceh Syariah, service quality affects customer trust at Bank Aceh Syariah, satisfaction affects customer loyalty at Bank Aceh Syariah, trust has an effect on customer loyalty of Bank Aceh Syariah, Satisfaction partially mediates the effect of service quality on customer loyalty of Bank Aceh Syariah, and Trust partially mediates the effect of service quality on customer loyalty of Bank Aceh Syariah.